Simplify
Expand
Factorise
Solve
100

6x + (-9) + 5x - 1

11x - 10

100

Expand:

(2x + 5)(7a - 4b)

14ax - 8bx + 35a - 20b

100

Factorise completely:

-16m + 8mn - 40n + 56

8 (-2m + mn - 5n + 12)


or

-8 (2m - mn + 5n - 12)

100

x - 8 = -5

3

200

- (2b + d -9) + 5

-2b - d +14

200

Expand:

(9g - 4h)( - g + 5h)

-9g2 + 49gh - 20h2

200

Factorise completely:

20ab2c + 30a2b3c - 21abc2

abc (20b + 30ab2c - 21c)

200

x2  =  100

10 or -10

300

(16a^2bc^3)/(24bc

(2a^2c)/3

300

Expand:

-(3m + 5p)(m - p)

- (3m2 - 3mp + 5mp - 5p2)

= - (3m2 + 2mp - 5p2)

= - 3m2 - 2mp + 5p2

300

Factorise completely:

(Clue:  Can you see a common factor without expanding the expression?)

2(x+1) - y (x+1)

2(x+1) - y (x+1) = (x+1)(2-y)

300

6a - 5 = 2a + 11

a = 4

400

20 - x = -10x - 34

x = -6

500

3(-2m +5) - 4 = 0

m = 11/6 or 1 5/6

Click to zoom